BUILDING DIVERSITY WITH MULTICULTURAL EDUCATION TO PREVENT BULLYING IN ELEMENTARY SCHOOLS - Arcilia Intan Permadani; Ratih Kurniasih; Rendo Fahestama (Journal of Pedagogical Content Knowledge, 2026)
Multicultural education provides students with the knowledge, attitudes, and social skills necessary to become responsible and respectful citizens in a diverse society. In the context of Indonesia, which is characterized by extensive ethnic, cultural, religious, linguistic, and social diversity, multicultural education is highly relevant to students’ everyday lives. Differences are an integral part of Indonesian society; therefore, education needs to prepare students to understand, appreciate, and respond positively to diversity. At the elementary school level, multicultural education plays an important role because childhood is a critical period for developing character, social attitudes, and patterns of interaction with others. The implementation of multicultural education can serve as an educational strategy for preventing potential social conflict by introducing values such as tolerance, empathy, equality, nationalism, cooperation, and mutual respect from an early age. These values can be integrated into classroom learning, curriculum content, school activities, and daily interactions within the school environment. Through meaningful multicultural learning experiences, students can develop an awareness that cultural and social differences should not become reasons for discrimination, prejudice, or conflict. Instead, diversity can be viewed as a valuable resource for strengthening social cohesion and national unity. Multicultural education can also create an inclusive learning environment in which students from different backgrounds have equal opportunities to participate, communicate, collaborate, and express their identities. Therefore, the implementation of multicultural education in elementary schools is an important effort to develop students who are tolerant, empathetic, inclusive, and committed to maintaining harmony within Indonesia’s diverse society.